EXTRACTION-PHOTOMETRIC DETERMINATION OF NORSULFAZOLE USING TRIMETHYLTHIONIN BASIC DYE (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The interaction of the norsulfazole sodium salt with trimethylthionin (Azur II) basic dye has been studied. The optimal conditions for formation of ionic associate have been estimated. It has been revealed that the forming ionic associate may be isolated by means of onefold extraction during 0,.5 min by chloroform in the pH 8.5–9.5  range under equal volumes of organic and aqueous phases. The obeying to the photometry main law is observed within the 3.75–40.0 mcg/mL norsulfazole concentration range, the light adsorption molar coefficient average value at 640 nm wavelength ε=20000±300 (L·mol–1·cm–1). The norsulfazole sodium salt interacts with trimethylthionin in 1:1 molar ratio.
Keywords: norsulfazole sodium salt; trimethylthionin; ionic associate; extraction; molar ratio